Thermoeconomic analysis for hybrid solar Brayton cycles operating with different working fluids (2024)
A Brayton cycle analysis with regeneration fed by heat input from a central concentration solar energy tower and a combustion chamber that uses natural gas is presented. The thermodynamic model includes the irreversibility of the different components of a conventional Brayton cycle system and a solar concentration system through energy and exergy considerations. The environmental conditions of Barranquilla are used for the plant analysis using different working fluids throughout the day, where the carbon dioxide cycle presents an overall efficiency of 28.8 %, the cycle with air efficiency is 26.6 %, and the Helium cycle is 20.2 %. The model considers the energy flows within the plant and the exergy destruction. In this sense, the solar concentration system contributes an energy fraction of 0.209 when operating with air, while the exergy destruction fraction is 0.189 when operating with carbon dioxide when solar radiation is maximum. Finally, an estimation of the Levelized Cost of Energy is presented.